2007
DOI: 10.1128/iai.01734-06
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution and Patterns of Dissemination of the JP2 Clone of Aggregatibacter ( Actinobacillus ) actinomycetemcomitans

Abstract: The natural history, microevolution, and patterns of interindividual transmission and global dissemination of the JP2 clone of Aggregatibacter (Actinobacillus) actinomycetemcomitans were studied by population genetic analysis. The JP2 clone is strongly associated with aggressive periodontitis in adolescents of African descent and differs from other clones of the species by several genetic peculiarities, including a 530-bp deletion in the promoter region of the leukotoxin gene operon, which results in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
176
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(184 citation statements)
references
References 55 publications
4
176
1
3
Order By: Relevance
“…A recent study which analyzed the multilocus sequence of 82 A. actinomycetemcomitans strains, including 66 JP2 clones, indicated that the JP2 clone initially emerged as a distinct genotype in the part of Africa along the Mediterranean approximately 2,400 years ago (22). Later, this specific strain appeared to spread throughout the whole continent of Africa (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study which analyzed the multilocus sequence of 82 A. actinomycetemcomitans strains, including 66 JP2 clones, indicated that the JP2 clone initially emerged as a distinct genotype in the part of Africa along the Mediterranean approximately 2,400 years ago (22). Later, this specific strain appeared to spread throughout the whole continent of Africa (22).…”
Section: Discussionmentioning
confidence: 99%
“…Among genetic differences found in A. actinomycetemcomitans, the 530-bp deletion in the promoter region of the LTX gene operon increases LTX activity by the JP2 clone, the so-called highly leukotoxic A. actinomycetemcomitans clone. On the other hand, in some pathogenic strains of A. actinomycetemcomitans, termed minimally leukotoxic, the 530-bp deletion does not seem to occur (22); consequently, less LTX activity is observed. As a result, non-JP2 clones (e.g., A. actinomycetemcomitans strains 652 and ␥4) appear to be associated with a lesser severity of periodontal disease (11,30).…”
mentioning
confidence: 99%
“…This highly leukotoxic clone (JP2) has recently been reported to also colonize subjects with, by genotyping confirmed, North-European origin (Claesson et al, 2011). Clonal diversity analysis of JP2-like isolates have shown that all strains of this clone have a common ancestor from Northern Africa (Haubek et al, 2007). The high accumulation of this clone in subjects of African origin has indicated a possible host tropism, but could also be a result of the strict vertical transmission pattern of this bacterium Haubek 2010).…”
Section: Expression and Secretion Of A Actinomycetemcomitans Leukotoxinmentioning
confidence: 99%
“…Longitudinal studies have shown that periodontally healthy children that harbour A. actinomyctemcomitans have an increased risk to develop Localized aggressive periodontitis (LAP) (Van der Velden et al, 2006;Fine et al, 2007). A specific clone (JP2) is strongly associated with LAP in subjects of African origin, and differs from other clones of this species by several genetic peculiarities, including a 530-bp deletion in the promotor region of the leukotoxin gene operon, which results in an enhanced expression of leukotoxin (Brogan et al 1994;Haubek et al, 2007Haubek et al, & 2008. Healthy adolescents harbouring this clone were shown to have an 18-fold increased risk to develop periodontal attachment loss within a 2-year follow up period compared to the A. actinomycetemcomitans negative controls (Haubek et al, 2008).…”
mentioning
confidence: 99%
“…Other than the inserted or deleted segments, all of the remaining sequences in the ltx promoter and in orfA are virtually identical in minimally leukotoxic and hyperleukotoxic strains (Brogan et al, 1994;He et al, 1999). For example, the hyperleukotoxic JP2 strain expresses approximately 10-fold higher levels of cytotoxic activity than minimally leukotoxic strains and has been found extensively in localized aggressive periodontitis patients in United States, Northern African and European populations (Cortelli et al, 2005;Haraszthy et al, 2000;Haubek et al, 1997Haubek et al, , 2001Haubek et al, , 2004Haubek et al, , 2007. This strain possesses a 530 bp deletion that truncates orfA (Brogan et al, 1994), suggesting either that orfA plays a role in regulating ltx expression or that the truncation of orfA in A. actinomycetemcomitans JP2 increases transcription simply by bringing the ltx promoter into closer proximity to ltxCABD (Kolodrubetz et al, 1996).…”
Section: Introductionmentioning
confidence: 99%